Developing Prezi Media with ASSURE Model for History Learning of the Eleventh Grade - Shintya Elisva; Nurul Umamah; Sumardi Sumardi (JURNAL HISTORICA, 2019)
Information technology and communication based learning is a necessity for today's students who are skilled at technology. For this reason, media and learning resources need to be developed. Based on performance analysis, it shows that students are facilitated by media only 25% and learning resources are only 17%. The results of characteristic analysis of students at SMAN 3 Jember, Ambulu Senior High School, and Rambipuji High School indicate that: (1) 40% of students were able to recall the material; (2) audio learning style is 33.37%, visual is 57.17%, kinesthetic is 14.66%; (3) 51.51% of students obtain high motivation. The purpose of this research is to develop a validated and effective Prezi media for learning class XI history subject. This study utilizes the ASSURE development model. Data collection techniques used were observation techniques, questionnaires, and tests. The results of expert validation on the development of Prezi namely, material experts are 80% means good qualifications, media experts and learning design are 80% means with good qualifications, and linguists obtain 86% means very good qualifications. The results of testing users 1 and 2 are 88% and 89% means very good qualifications. The effectiveness usage of Prezi in small groups is 0.6% with moderate qualifications and large groups of 0.73% means high qualifications. Based on the results obtained, Prezi media is suitable and effectively used as a media and source of learning. Keywords: Developing, Prezi, History Learning, ASSURE